Putative interaction site for membrane phospholipids controls activation of TRPA1 channel at physiological membrane potentials - Macikova, Lucie; Sinica, Viktor; Kadkova, Anna; Villette, Sandrine; Ciaccafava, Alexandre; Faherty, Jonathan; Lecomte, Sophie; Alves, Isabel D; Vlachova, Viktorie (The FEBS journal, 2019)
The transient receptor potential ankyrin 1 (TRPA1) channel is a polymodal sensor of environmental irritant compounds, endogenous proalgesic agents, and cold. Upon activation, TRPA1 channels increase cellular calcium levels via direct permeation and trigger signaling pathways that hydrolyze phosphatidylinositol-4,5-bisphosphate (PIP2 ) in the inner membrane leaflet. Our objective was to determine the extent to which a putative PIP2 -interaction site (Y1006-Q1031) is involved in TRPA1 regulation. The interactions of two specific peptides (L992-N1008 and T1003-P1034) with model lipid membranes were characterized by biophysical approaches to obtain information about affinity, peptide secondary structure, and peptide effect in the lipid organization. The results indicate that the two peptides interact with lipid membranes only if PIP2 is present and their affinities depend on the presence of calcium. Using whole-cell electrophysiology, we demonstrate that mutation at F1020 produced channels with faster activation kinetics and with a rightward shifted voltage-dependent activation curve by altering the allosteric constant that couples voltage sensing to pore opening. We assert that the presence of PIP2 is essential for the interaction of the two peptide sequences with the lipid membrane. The putative phosphoinositide-interacting domain comprising the highly conserved F1020 contributes to the stabilization of the TRPA1 channel gate.
Keywords: Membrane Potentials; Calcium; TRP channel; TRPA1 Cation Channel; HEK293 buňky; vápník; signální transdukce; HEK293 Cells; sekundární struktura proteinů; Phosphatidylinositol 4,5-Diphosphate; Protein Structure, Secondary; metabolismus lipidů; Signal Transduction; membránové potenciály; gating; kinetika; lidé; biofyzikální jevy; Biophysical Phenomena; Phospholipids; Humans; Lipid Metabolism; fosfatidylinositol-4,5-difosfát; fosfolipidy; Peptides; kationtový kanál TRPA1; peptidy; rectification; ankyrin transient receptor potential; Kinetics; peptide-lipid interaction